2006
DOI: 10.1210/en.2006-0394
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Ontogeny of Mammalian Ovarian Neurons

Abstract: Mammalian ovaries contain sympathetic neurons expressing the low affinity neurotropin receptor (p75NTR). To date neither the role these neurons might play in ovarian physiology nor their embryological origin is known. Immunohistochemistry was used to detect postnatal changes in distribution and number of both p75NTR-positive and tyrosine hydroxylase-positive neurons in rhesus monkey ovaries. Pig fetuses were used to map the pathway of ovarian neuronal migration during embryonic development. Antiserum to p75NTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…This conclusion is in keeping with findings in rhesus monkeys showing that both the density and composition of the sympathetic ovarian innervation, in addition to the number of intrinsic catecholaminergic neurons present in the ovary of this species, reach a maximum near the time of puberty (16,18). It would not be unreasonable to expect that similar developmental changes in sympathetic input to the ovary occur in humans because the adult human ovary not only contains TH-positive nerve terminals but also responds to depolarization with incorporation and release of NE (37).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This conclusion is in keeping with findings in rhesus monkeys showing that both the density and composition of the sympathetic ovarian innervation, in addition to the number of intrinsic catecholaminergic neurons present in the ovary of this species, reach a maximum near the time of puberty (16,18). It would not be unreasonable to expect that similar developmental changes in sympathetic input to the ovary occur in humans because the adult human ovary not only contains TH-positive nerve terminals but also responds to depolarization with incorporation and release of NE (37).…”
Section: Discussionsupporting
confidence: 91%
“…Total incorporation of 3 H-NE into ovarian tissue increased moderately during the neonatal-infantile period (d [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and then abruptly during the second half of juvenile development (d 26 -30), remaining elevated at puberty (d [31][32][33][34][35], and after the first ovulation (d 40) (Fig. 1A).…”
Section: Incorporation Of 3 H-ne During Postnatal Ovarian Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that these are extrinsic nerves entering the gonad by innervation, and the existence of intrinsic neurons in the fetal testis has not been clearly established. Nevertheless, intrinsic neurons have been identified in postnatal testes of primates (Mayerhofer et al 1996a;Mayerhofer et al 1999;Frungieri et al 2000) and also in fetal ovaries of both humans and pigs (Anesetti et al 2001;Dees et al 2006). In rodent ovaries, there appear to be few or no intrinsic neurons (D'Albora and Barcia 1996; D' Albora et al 2000).…”
Section: Testis Innervationmentioning
confidence: 99%
“…In contrast, the results of Sen and Hammes [9] indicated that loss of AR function in granulosa cells is sufficient to effect dysregulation of the estrous cycle, suggesting possible generation of a negative modulator of cycle regulation. Ovaries of various mammalian species are subjected to sympathetic innervation to form an intrinsic neural network, which changes with age and declines with reproduction aging [162]. If the putative ovarian negative regulator generated by the loss of granulosa AR acts through the ovarian neural reflex, such an effect would not be observed in Wt hosts transplanted with mutant AR ÀEX3 ovaries.…”
Section: Ar Roles In Ovarian Folliculogenesis and Fertilitymentioning
confidence: 99%